Face processing improvements in prosopagnosia: successes and failures over the last 50 years - DeGutis, Joseph M.; Chiu, Christopher; Grosso, Mallory E.; Cohan, Sarah (Frontiers in Human Neuroscience, 2014)
Clinicians and researchers have widely believed that face processing cannot be improved in prosopagnosia. Though more than a dozen reported studies have attempted to enhance face processing in prosopagnosics over the last 50 years, evidence for effective treatment approaches has only begun to emerge. Here, we review the current literature on spontaneous recovery in acquired prosopagnosia (AP), as well as treatment attempts in acquired and developmental prosopagnosia (DP), differentiating between compensatory and remedial approaches. We find that for AP, rather than remedial methods, strategic compensatory training such as verbalizing distinctive facial features has shown to be the most effective approach (despite limited evidence of generalization). In children with DP, compensatory training has also shown some effectiveness. In adults with DP, two recent larger-scale studies, one using remedial training and another administering oxytocin, have demonstrated group-level improvements and evidence of generalization. These results suggest that DPs, perhaps because of their more intact face processing infrastructure, may benefit more from treatments targeting face processing than APs.